Association Analysis of Insulin Resistance and Osteoporosis Risk in Chinese Patients with T2DM - Wang X (Dove Medical Press, 2021)
Xinshui Wang,1 Lijuan Jiang,2 Xiaonan Shao3 1Department of Endocrinology, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 2Department of Clinical Laboratory, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 3Department of Nuclear Medicine, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of ChinaCorrespondence: Lijuan JiangDepartment of Clinical Laboratory, the Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of ChinaTel +86-0-13776885831Fax +86-0519-86621235Email czyyjlj@126.comBackground: To explore the relationship between insulin resistance and osteoporosis risk in Chinese patients with type 2 diabetes mellitus (T2DM).Methods: A total of 234 T2DM patients were retrospectively analyzed, and their lumbar bone mineral density (BMD) and insulin resistance using C-peptide-based homeostasis model of insulin resistance [HOMA-IR (CP)] were assessed. Univariate and multivariable logistic regression methods were used to evaluate the association between HOMA-IR (CP) and osteoporosis, and subgroup analysis was performed on female and male patients.Results: After fully adjusting the covariates, the association between HOMA-IR (CP) and osteoporosis was only significant in female patients (P = 0.022); the interaction effect with gender was significant (P for interaction < 0.05). Curve fitting showed that the relationship between HOMA-IR (CP) and osteoporosis in women was nonlinear. When HOMA-IR (CP) is < 4.00, its effect on osteoporosis was not significant (P = 0.474); when HOMA-IR (CP) is > 4.00, the risk of osteoporosis increased significantly, with OR = 26.88 (95% CI: 2.75– 262.69, P = 0.005). The relationship between insulin resistance and osteoporosis risk in T2DM patients is significantly affected by gender.Conclusion: The higher the degree of insulin resistance in female patients, the greater the risk of osteoporosis, but the two are not linearly associated.Keywords: type 2 diabetes mellitus, insulin resistance, osteoporosis, bone mineral density, homeostasis model assessment for insulin resistance